Sistem Pendukung Keputusan Penentuan Home industry Menggunakan Metode Topsis - Bob Aziz; Andrianingsih (KITA Institute, 2022)
The research objective is a system that can determine the right home industry business in the midst of business competition, and to implement the TOPSIS technique when the Decision Support object sets the home industry right in the midst of intense competition. The categories used in this observation are initial capital, monthly working budget analysis, profit analysis, whether the selected business category is a variety of businesses with different types of enthusiasts, and there are various competitors with the same type of business. The data is taken based on the Home industry type of food. Decision Support System designed using TOPSIS technique, PHP programming language, Laravel framework, MySQL as database management, and Black-box Testing as the method used to test the functionality of the system that has been built. Based on the tests applied using the Black-box Testing technique, the conclusion of the test shows that the system made in series is as expected. In other words, the system designed will be able to help users who are just starting a Home industry business in determining which products to sell.